Assessment of the AQUIOS flow cytometer – An automated sample preparation system for CD4 lymphocyte PanLeucogating enumeration - Rhodes, Daniel (Afr J Lab Med, 2019)
BACKGROUND: Flow cytometry has been the approach of choice for enumerating and documenting CD4-cell decline in HIV monitoring. Beckman Coulter has developed a single platform test for CD4+ T-cell lymphocyte count and percentage using PanLeucogating (PLG) technology on the automated AQUIOS flow cytometer (AQUIOS PLG). OBJECTIVES: This study compared the performance of AQUIOS PLG with the Flowcare PLG method and performed a reference interval for comparison with those previously published. METHODS: The study was conducted between November 2014 and March 2015 at 5 different centres located in Canada; Paris, France; Lyon, France; the United States; and South Africa. Two-hundred and forty samples from HIV-positive adult and paediatric patients were used to compare the performances of AQUIOS PLG and Flowcare PLG on a FC500 flow cytometer (Flowcare PLG) in determining CD4+ absolute count and percentage. A reference interval was determined using 155 samples from healthy, non-HIV adults. Workflow was investigated testing 440 samples over 5 days. RESULTS: Mean absolute and relative count bias between AQUIOS PLG and Flowcare PLG was −41 cells/µL and −7.8%. Upward and downward misclassification at various CD4 thresholds was ≤ 2.4% and ≤ 11.1%. The 95% reference interval (2.5th – 97.5th) for the CD4+ count was 453–1534 cells/µL and the percentage was 30.5% – 63.4%. The workflow showed an average number of HIV samples tested as 17.5 per hour or 122.5 per 8-hour shift for one technician, including passing quality controls. CONCLUSION: The AQUIOS PLG merges desirable aspects from conventional flow cytometer systems (high throughput, precision and accuracy, external quality assessment compatibility) with low technical operating skill requirements for automated, single platform systems.